Processamento de cama de aves e dejetos bovinos por meio da vermicompostagem - Ferreira, Elisiane (2017)
With the increase in specialization in agricultural activities, especially in relation to poultry farming and dairy production, the generation of organic waste has become an environmental problem. The reuse of these residues in the form of fertilizers is a good alternative allowing the partial replacement of the mineral fertilization of the crops, however, it is necessary to adopt a treatment system for their reuse. The vermicompost has been widely used for the transformation of organic waste, where the worms act to accelerate the stabilization process. The objective of the project was to evaluate the processing of bed of poultry and bovine manure by vermicomposting. The work was developed at UNEPE of Composting of the Universidade Tecnológica Federal do Paraná - DV. It was constituted of sample units of masonry with coverage of 0.3 m³ (1.00x1.00x0.30) where four treatments were implanted composed of 100% bovine manure, 75% bovine manure + 25% poultry bed, 50% manure Bovine + 50% poultry bed and 25% bovine manure + 75% poultry bed. The experimental design was a randomized block design, with four replications, totaling 16 sample units. The proportions were based on the wet mass of the materials, where each unit contained 300 kg of homogenised material, the first treatment consisted of 300 kg of bovine manure, the second one per 225 kg of bovine manure and 75 kg of bed The third for 150 kg of bovine manure and 150 kg of poultry litter and the last for 75 kg of bovine manure and 225 kg of poultry litter. In each sample unit was added 1000 ml of California red worm (Eisenia foetida). During the whole vermicompost process, the samples were collected, and after analysis of organic carbon (C) content, nitrogen (N), phosphorus (P) and potassium (K) were analyzed. The process lasted 100 days, in which the volume and mass of vermicompost produced, the amount of surviving earthworms, C and N of biomass and CO2 emission rate were quantified. It is identified as a result that the addition of poultry litter, even to a lesser extent, impairs the survival of the worms, but this mixture does not interfere with the amount of vermicompost produced at the end of the process, generating satisfactory volume. The poultry bed mixed with bovine manure raises the C and N contents of the microbial biomass, not affecting K contents, elevates P and N content, decreasing the C: N ratio, thus improving the availability of nutrients. The addition of the bed of birds increases the mortality of the worms making the process dependent only on the microbial activity for maturation, a period of more than 100 days is necessary for its suitability of use.